'We Had Loved Her so Much—The Republic!': West Germany's Red Cells and the New Left's Development After 1968. Issue 3 (2nd October 2021) - Dapprich, Matthias
Abstract : In this paper, it is argued that aspects of political theory provide a far more useful basis for analysing the developments of the West German New Left than merely placing these developments in the context of the broader societal changes during the 1970s and 1980s. From understanding the formation and progress of the transitory Red Cells movement after 1968 as a blueprint to the overall development of the New Left, the author demonstrates the importance of theory formation on the most influential factions', i.e. Maoist K-Gruppen and Marxist Group, political practice. Furthermore, the analysis offers an explanation for why the demise of K-Gruppen was inherent in the surge of new social movements in the late 1970s, while the Marxist Group grew until its dissolution in 1991. In light of the historical developments in West Germany, it is questionable whether the political left is or should be a vox populi.